2014
DOI: 10.1093/jnci/dju088
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Insulin-like Growth Factor-1 Score to Assess Hepatic Reserve in Hepatocellular Carcinoma

Abstract: BackgroundChild-Turcotte-Pugh (CTP) score is the standard tool to assess hepatic reserve in hepatocellular carcinoma (HCC), and CTP-A is the classic group for active therapy. However, CTP stratification accuracy has been questioned. We hypothesized that plasma insulin-like growth factor 1 (IGF-1) is a valid surrogate for hepatic reserve to replace the subjective parameters in CTP score to improve its prognostic accuracy.MethodsWe retrospectively tested plasma IGF-1 levels in the training set (n = 310) from MD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…[10] Cut-off points for total bilirubin, albumin, and PT are identical with those in the original CTP classification. Cut-off points for IGF-1, which were previously derived from recursive partitioning methods and survival analyses, are 26 and 50 ng/mL.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] Cut-off points for total bilirubin, albumin, and PT are identical with those in the original CTP classification. Cut-off points for IGF-1, which were previously derived from recursive partitioning methods and survival analyses, are 26 and 50 ng/mL.…”
Section: Methodsmentioning
confidence: 99%
“…[7–9] Therefore, Kaseb et al constructed a modified CTP classification system (IGF-CTP) to predict survival in patients with HCC by replacing the two subjective parameters in the traditional CTP system with IGF-1 level (S1 Table). [10] They observed that the IGF-CTP classification provided better risk stratification than the original CTP classification in both American and international validation cohorts. [10, 11] However, the value of the IGF-CTP classification for prognostic stratification has not been evaluated in chronic hepatitis B (CHB) endemic areas, such the Asia-Pacific region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1113 Overall survival (OS) was defined as the time between HCC diagnosis and death (as a result of all causes) or end of follow-up (censored observations). Underlying cirrhosis was determined by pathological findings (diagnostic biopsies) and by computed tomography scans.…”
Section: Methodsmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the fifth most common cancer worldwide and the third leading cause of cancer-associated mortality (1), which explains the importance of identifying novel early diagnostic markers and therapeutic targets (2). HCC primarily develops from cirrhosis caused by chronic infection with hepatitis B virus or hepatitis C virus (HCV), alcoholic injury, and, to a lesser extent, from genetically determined disorders (3).…”
Section: Introductionmentioning
confidence: 99%